Research papers Structural insights into the substrate-binding proteins Mce1A and Mce4A from Mycobacterium tuberculosis. (2021) - Asthana, Pooja; Singh, Dhirendra; Pedersen, Jan Skov; Hyno¨nen, Mikko J.; Sulu, Ramita; Murthy, Abhinandan V.; Laitaoja, Mikko; Ja¨nis, Janne; Riley, Lee W.; Venkatesan, Rajaram
No abstract available